The Relevance of Hadith in the Digital World: Hate Speech on Social Media - Darin Rihhadatul ‘Aisy; Endad Musaddad (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
This study examines the urgency of social media ethics in the perspective of hadith amid the rise of negative comments. The aim is to highlight the Prophet's words as guidelines for polite communication. A qualitative method of literature study was used with sources from hadith books and scientific literature. The results show that hate speech and digital bullying are contrary to Islamic teachings. The Prophetic Hadith encourages the creation of a healthy and moral digital space.